RELATIONSHIP OF BODY IMAGE WITH EATING DISORDER IN FEMALE ADOLESCENT - Senna Virgandiri; Dhian Ririn Lestari; Rika Vira Zwagery (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
In adolescence there is an increased awareness of the body image. The majority of femaleadolescent think that a thin, slim and small body is a perfect form. The existence ofchanges in the increase in body fat during puberty causes female often feel less satisfiedand causes adolescents to control body weight to achieve the ideal body shape concept.The aim of study to find out the relationship between body image with eating disorderin female adolescent. This study used an analytical method with a cross sectional designthat included 80 students of SMK Borneo Lestari. Subjects were chosen by stratifiedrandom sampling technique. The research instrument was a Multidimensional BodySelf Relations Questionnaire Appearance Scale (MBSRQ-AS) questionnaire and EatingAttitude Test (EAT) questionnaire which was modified. Data analysis using spearmancorrelation test. The results showed the majority of respondents had a positive bodyimage (81.9%) and had a risk of mild eating disorders (56.3%). The Spearman correlationtest showed that there was no significant relationship between body image and eatingdisorder in female adolescent pv = 0.717 (Î±> 0.05). This shows that the higher the totalbody image of a person, the higher the total score of eating disorders, which means themore positive the body image will be risk to mild of eating disorders.